2008
DOI: 10.1021/jp8020326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvent on Two-Photon Absorption by Vinyl Benzene Derivatives

Abstract: Two-photon absorption cross sections and spectral profiles were determined for three centrosymmetric vinyl benzenes in solvents of differing polarity and polarizability. The data do not correlate with parameters that characterize dielectric properties of the solvents. Rather, the effect of solvent depends on the solute, and even subtle structural changes in the latter can result in pronounced solvent-dependent differences in the absorption cross section. Our data highlight the need for more sophisticated model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 61 publications
7
40
0
1
Order By: Relevance
“…37 On the other hand, several studies have shown that two-photon cross-section can be minimally affected by solvent for some fluorophores. 3133 One sees slightly different trend for the S38C sample, where the cross-section does change upon addition of calcium. This particular system illustrated a number of different properties, which illustrated the sensitivity of the two-photon method (see below).…”
Section: Resultsmentioning
confidence: 92%
“…37 On the other hand, several studies have shown that two-photon cross-section can be minimally affected by solvent for some fluorophores. 3133 One sees slightly different trend for the S38C sample, where the cross-section does change upon addition of calcium. This particular system illustrated a number of different properties, which illustrated the sensitivity of the two-photon method (see below).…”
Section: Resultsmentioning
confidence: 92%
“…As far as the modeling of the solvent effect on linear and nonlinear optical properties is concerned, we note that recent experimental studies [41] have shown that explicit solvent models, such as those based on quantum mechanics/molecular mechanics (QM/MM) methods [42] also in combination with analytical response approaches, [43] can outperform implicit continuum models in the description of the solvent effect in TPA. However, in the present work we aim at simulating spectra showing clear vibrational structures, and vibronic HT effects.…”
Section: Solvent Modelmentioning
confidence: 99%
“…Several reports have been made where changes of for example the TPA crosssection of a series of conjugated organic molecules have been rationalised quite successfully using calculations carried out with the response formulation and not considering solvent effects [32,33]. In particular, the solvent effect on the TPA cross-section of larger conjugated organic molecules has hardly been studied experimentally possibly due to the tedious experiments needed in order to obtain reliable results [34]. In terms of pure theoretical efforts, a few reports have been made where a dielectric continuum model was used (see for example Ref.…”
Section: Introductionmentioning
confidence: 99%